PENGARUH KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN NASABAH PADA BANK SAMPAH TEGEH SARI LESTARI - Atmaja, Ni Putu Cempaka Dharmadewi; Semiati, Ni Wayan; Agung, Anak Agung Putu (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
This study aims to re-examine the effect of service quality variables and price perceptions on customer satisfaction. This research was conducted on customers of the Tegeh Sari Lestari Waste Bank located at Jalan Gatot Subroto I No. 38 Tonja, North Denpasar District, Denpasar City, Bali. The population in this study were all customers of the Tegeh Sari Lestari Waste Bank with a total of 400 people. The number of samples is 80 people using the slovin method. Methods of data collection with interviews, questionnaire documentation and observation. The data analysis technique used was classical assumption test, multiple linear regression analysis, coefficient of determination, F test and t test using SPSS version 25.0 for Windows. Based on the test results, it can be concluded that service quality has a positive and significant effect on customer satisfaction which can be seen from the tcount value of 7.930 and the t-test significant value of 0.000 <0.05 so Ho is rejected and H1 is accepted. That price perception has a positive effect on customer satisfaction which can be seen from the t-value of 7.027 and the significant value of the t-test of 0.000 <0.05 so that Ho is rejected and H2 is accepted